Mapping the spatial and temporal extent of floods in South Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
A research project by CCAFS and the International Water Management Institute (IWMI) focuses on a moderate-resolution mapping of monsoon ﬂood risk areas in South Asia using satellite remote-sensing datasets. In the past, many studies were carried out in South Asia to investigate the hydrologic behaviour of the ﬂ oods and post-ﬂood event mapping using remote-sensing data. However, large-scale systematic monitoring of ﬂoods both spatially and temporally covering the whole of South Asia has been very limited.